Eternal God a study of God without time - Helm, Paul. (Oxford : Oxford University Press, 2010)
'Eternal God' offers a powerful defence of the view that God exists in timeless eternity. This classical Christian view is claimed by many theologians and philosophers to be incoherent but Helm rebuts this charge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: God -- Proof